A Study of Patterns of Thoracic Injuries in the Victims of Vehicular Incidents Brought to the GMCH Mortuary for Medicolegal Autopsies - Anurupa Choudhury1 , Himangshu Das 2 , Ravi Kumar Sharma3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study aims to highlight the pattern of thoracic injuries sustained by the victims of fatal roadtraffic accidents (RTA) brought to the GMCH Mortuary for medico legal autopsies. The study is an autopsybased observation during 1st April 2019 to 31st March 2020. In this study, incidence of thoracic injuryamong all cases of vehicular accident is 23.83%. A male preponderance (89%) was observed with a malefemale ratio of 7.7:1. Peak incidence was observed in the age group of 21-30 years (27.24%). In all cases,thoracic injuries are associated with external or internal injuries on other parts of the body. Pleura are themost commonly involved organs in the thoracic regions. Majority of the victims were pedestrians ((36.6 %)followed by two-wheelers (31.06%). The study indicates the pattern of thoracic injuries sustained along withthe trend of road traffic accidents in the region